2016
DOI: 10.1097/psy.0000000000000278
|View full text |Cite
|
Sign up to set email alerts
|

Association of Trait Resilience With Peritraumatic and Posttraumatic Stress in Patients With Myocardial Infarction

Abstract: Objective: Acute myocardial infarction (MI) is a life-threatening condition, leading to immediate fear and distress in many patients. Approximately 18% of patients develop posttraumatic stress disorder in the aftermath of MI. Trait resilience has shown to be a protective factor for the development of posttraumatic stress disorder. However, whether this buffering effect has already an impact on peritraumatic distress and applies to patients with MI is elusive. Methods: We investigated 98 consecutive patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Several of the included studies showed that younger people (Guler et al., 2009; Hari et al., 2010; Kronish et al., 2018; von Känel et al., 2011) and women (Fortin et al., 2013; Hari et al., 2010; Husain et al., 2017; Kronish et al., 2018; Meister, Princip, et al., 2016; Roberge et al., 2010; von Känel et al., 2011) are at higher risk of developing PTSD compared with older individuals and men, whereas several investigations could not confirm these results (Gao et al., 2015; Guler et al., 2009; Lima et al., 2018; Marke & Bennett, 2013; Sumner et al., 2015; Wikman et al., 2012). There is no research evidence to support the positive effect of socioeconomic status on an individual's risk of developing PTSD (Wikman et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the included studies showed that younger people (Guler et al., 2009; Hari et al., 2010; Kronish et al., 2018; von Känel et al., 2011) and women (Fortin et al., 2013; Hari et al., 2010; Husain et al., 2017; Kronish et al., 2018; Meister, Princip, et al., 2016; Roberge et al., 2010; von Känel et al., 2011) are at higher risk of developing PTSD compared with older individuals and men, whereas several investigations could not confirm these results (Gao et al., 2015; Guler et al., 2009; Lima et al., 2018; Marke & Bennett, 2013; Sumner et al., 2015; Wikman et al., 2012). There is no research evidence to support the positive effect of socioeconomic status on an individual's risk of developing PTSD (Wikman et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Findings also demonstrated associations between PTSD secondary to MI and certain personality traits, such as anxious attachment (Gao et al., 2015) or alexithymia, which results in difficulty identifying and expressing emotions (Gao et al., 2015; Marke & Bennett, 2013). In contrast, personality traits such as resilience, characterized by a sense of personal competence and acceptance of self and existence, were shown to be a protective factor for PTSD after MI (Meister, Princip, et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Still others have utilized the DSM-IV Criterion A2 by using three questions to assess peritraumatic fear, helplessness, and horror (Blix, Hansen, Birkeland, Nissen, & Heir, 2013;Boelen, 2015). In the myocardial infarction literature, multiple studies have assessed peritraumatic reactions using three questions about fear of dying, helplessness, and pain (Meister et al, 2016;von Känel, Hari, Schmid, Saner, & Begré, 2011;Wiedemar et al, 2008). However, we found the PDI to surpass other measures in terms of reliability and validity across populations and languages and in terms of frequency of use (the PDI was used in the majority of studies on peritraumatic distress in our literature search).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, not necessarily every patient develops PTSD after MI. A possible explanation for this observation could be individual protective factors, such as resilience (Meister et al, 2016 ). Resilience can be described as an optimal adaption process after critical life events or even as the positive outcome after traumatic events (Agaibi & Wilson, 2005 ; Meister et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%